أثرُ التَّعايش السّلمي في حماية الوطن في السُّنة النبويَّة دراسةٌ تحليليَّةٌ في ضوء الواقع المعاصر - Ismael, Ardawan Mustafa; Arif, Arif Ali (IIUM Press, International Islamic University Malaysia, 2019)
يعد التعايش السلمي ركنًا رئيسًا في حماية الوطن وازدهاره في جميع حلائب الحياة. وقد سعى البحث إلى استجلاء دور التعايش السلمي في حماية الوطن، وأبان أن المقصود بحبّ الوطن هو الانتماء إليه، والذبُّ عنه، والإسهام في بنائه إنسانيًا واجتماعيًا واقتصاديًا وعسكريًا، في ضوء الشريعة الإسلامية. كذلك، أوضح أن الأحاديث النبوية قد أصلت لمشروعية حب الوطن وضرورة حمايته، والاشتياق إلى الوطن، وأوجبت حمايته وحفظه، وعدت من مات في سبيل الوطن من تَعداد الشهداء، وشرعت الدعاء للوطن بالازدهار والتقدم، كذلك، حثت على الرباط في الوطن والمكوث فيه رغم المحن والشدائد. وألمع البحث إلى أن السنة النبوية سنّت مقوماتٍ رئيسةً للتعايش السلمي، مثل: العدل بين المواطنين، والمساواة بينهم، والاعتراف بالآخر الديني، وأقرت مبدأ التعددية العقائدية بين شرائح الوطن. وللتعايش السلمي ثمرات إيجابية في حماية الوطن، من أبرزها: تعميق الانتماء للوطن، وسعي المواطنين من أجل تقدم الوطن وانتعاشه في شتى حلائب الحياة، واستتباب الأمن الوطني. وفي خاتمة البحث تقييد لأهم النتائج والتوصيات. ****************************************************************************** Peaceful co-existence is a key pillar in protecting the country and its prosperity in all spheres of life. The research sought to clarify the role of peaceful co-existence in protecting the homeland. It pointed out that the meaning of loving the homeland is to belong to it, to defense it and to contribute to its building socially, economically and military, develop it in the light of Islamic law. It also denoted that the Prophet's Hadiths mentioned the loving of homeland and the need for its protection. It selected those who died for the sake of homeland as martyrs, and encouraged people to stay in their homelands even in tough circumstances. Making supplications for the country to prosper and progress. The research highlighted that the Prophet's Sunna has made major elements for peaceful co-existence, such as: justice among citizens, equality between them, recognition of other religions, and the principle of pluralism among the sects of the homeland. It declared that Peaceful coexistence has a positive effects on the protection of the homeland. The most important of these are: deepening of belonging to the homeland, pursuing of citizens for the advancement of the country and its recovery in various spheres of life and the establishment of national security. Eventually, it showed the main results and recommendations